Robust Tracking Control of Quadrotors Based on Differential Flatness: Simulations and Experiments - Poultney, Alexander; Kennedy, Christopher; Clayton, Garrett; Ashrafiuon, Hashem (IEEE/ASME transactions on mechatronics, 2018)
We introduce a new exponentially convergent trajectory tracking control law based on the fully nonlinear quadrotor model subject to unknown disturbances and modeling uncertainties. The approach takes advantage of the system's differential flatness property to relate the second time derivative of linear accelerations (snap) to the roll and pitch moments. Using these model-based relations, the closed-loop system is transformed to follow an exponentially stable error dynamics that are robust to unknown disturbances and uncertainties bounded on a compact set. It is proven that the control law exponentially stabilizes the position and yaw tracking errors, while the roll and pitch angle tracking errors are ultimately bounded. Simulations and experimental results under windy conditions and without disturbance estimation, demonstrate the effectiveness and robustness of the approach.